Four-Tier Heat and Temperature Diagnostic Test (4T-HTDT) to Identify Student Misconceptions - Sukarelawan, Moh. Irma; Sriyanto, Sriyanto; Puspitasari, Ariati Dina; Sulisworo, Dwi; Hikmah, Ulfiana Nurul (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2021)
There are limited studies on the diagnosis of heat and temperature misconceptions using a four-tier instrument diagnostic test. Therefore, this study aims to identify misconceptions in heat and temperature material. The survey research was conducted on 164 students at SMAN 2 Bantul. Students were selected using a convenience sampling technique. Identification of student misconceptions using the Four Tier Heat and Temperature Diagnostic Test (4T-HTDT). Students' conceptual understanding is calculated using the percentage technique. The results of this study indicate that there are still many students who have misconceptions on the concept of "heat-temperature as an extensive quantity" and "heat-temperature depends on material objects". The findings are expected to be a strategic step for designing appropriate remedial teaching.